Psychological well-being para perempuan bekerja: Bagaimana peran dukungan sosial? - Waskito Rizky Ramadhani; IGGA. Noviekayati; Aliffia Ananta (INNER: Journal of Psychological Research, 2023)
Abstract This research is aiming to find out the relationship between social support and psychological well-being among working women. It is quantitative correlational research. The subjects of this research are 96 working women in Surabaya. The method of data collection in non-parametric this research is carried out by giving an online questionnaire using Google form and the Likert scale. The data analysis technique in this research obtains 0.206 for the correlation score. It means that there is a positive relationship between social support and the psychological well-being of working women. Keywords: Psychological well-being, Social supports, Working women